Ecthyma gangrenosum, a skin manifestation of Pseudomonas aeruginosa sepsis in a previously healthy child: A case report. Issue 2 (January 2017) - Biscaye, Stephanie; Demonchy, Diane; Afanetti, Mickael; Dupont, Audrey; Haas, Herve; Tran, Antoine
Abstract: Rationale: Ecthyma gangrenosum (Eg) is a necrotic lesion that is mostly seen in immunocompromised patients. It reflects a severe sepsis, possibly caused by Pseudomonas aeruginosa (Pa). Patient concerns: A healthy 3-year-old girl admitted to the Pediatric Emergency Department presented a sepsis-associated purpura with neurological and respiratory distress. Interventions: An empiric antibiotherapy (anti-meningococcal) was prescribed. Diagnoses: Forty-eight hours after admission, blood and wound cultures were positive for Pa . As a result, the decision was made to change the antibiotic therapy. Unfortunately, on day 3, the patient died. Exhaustive immunologic tests are presently being carried out. Outcomes: Eg caused by Pa is uncommon in healthy children, and purpura sepsis is usually caused by Neisseria meningitides infection. Lessons: Eg should be recognized rapidly so that the appropriate treatment can be prescribed as quickly as possible.